Simulation of Pharyngeal Airway Interaction with Air Flow Using Low-Re Turbulence Model. (21st March 2011) - Rasani, M. R.; Inthavong, K.; Tu, J. Y.
Abstract : This paper aims to simulate the interaction between a simplified tongue replica with expiratory air flow considering the flow in the pharyngeal airway to be turbulent. A three-dimensional model with a low-Re SST turbulence model is adopted. An Arbitrary Eulerian-Lagrangian description for the fluid governing equation is coupled with the Lagrangian structural solver via a partitioned approach, allowing deformation of the fluid domain to be captured. Both the three-dimensional flow features and collapsibility of the tongue are presented. In addition, examining initial constriction height ranging from 0.8 mm to 11.0 mm and tongue replica modulus from 1.25 MPa to 2.25 MPa, the influence of both of these parameters on the flow rate and collapsibility of the tongue is also investigated and discussed. Numerical simulations confirm expected predisposition of apneic patients with narrower airway opening to flow obstruction and suggest much severe tongue collapsibility if the pharyngeal flow regime is turbulent compared to laminar.